The role of interstimulus interval and "Stimulus‐type" in prepotent response inhibition abilities in people with ASD: A quantitative and qualitative review. Issue 11 (19th April 2016) - Kuiper, Marieke W.M.; Verhoeven, Elisabeth W.M.; Geurts, Hilde M.
Abstract : Autism spectrum disorders (ASD) are associated with prepotent response inhibition difficulties. However, the large variation between studies suggests that understudied factors, such as interstimulus interval (ISI) and "stimulus‐type" (both hypothesized proxies of stressors influencing arousal), might influence the inhibitory abilities of people with ASD. Using meta‐analysis, we tested whether differences in prepotent response inhibition between people with and without ASD was influenced by ISI. There was not enough variation in "stimulus‐type" between the studies to include it as a moderator. Thirty‐seven studies met inclusion criteria, with a combined sample size of 950 people with ASD and 966 typically developing controls. Additionally, a qualitative review including studies comparing a neutral and an arousing condition in one experiment was performed to examine whether fast ISI or specific arousing stimuli directly influence prepotent response inhibition. The meta‐analysis indicated that ISI was not a relevant moderator. The qualitative review showed that ISI and "stimulus‐type" had the same effect for both groups. Although all studies regarding ISI indicated that fast ISI worsened performance, different types of stimuli had either a positive or a negative influence. This could suggest that distinctive stimuli might affect arousal differently. While we replicated the inhibition difficulties in people with ASD ( g = .51), our results do not show strong ASD‐specific effects of ISI or "stimulus‐type" on inhibition. Nonetheless, ISI and "stimulus‐type" do seem to influence performance. Future research focusing on potential underlying factors (e.g., baseline physiological arousal) is needed to examine why this is the case. Autism Res 2016, 9: 1124–1141 . © 2016 International Society for Autism Research, Wiley Periodicals, Inc.